Preliminary characterization of exopolysaccharides produced by Abortiporus biennis in submerged fermentation - Long, Zhangde; Liu, Hong; Li, Jigang; Sun, Jiansheng; Xue, Yun; Hu, Zhizhong; Su, Zan; Xu, Chunping; Yan, Jing-Kun (Penerbit Universiti Kebangsaan Malaysia, 2019)
Abortiporus biennis is a rare edible and medicinal mushroom that is valuable in traditional Chinese medicine. Exopolysaccharides (EPSs) as valuable metabolites have been harvested from fermentation broths of A. biennis. However, studies on preliminary characterisations and bioactivities of A. biennis EPSs are lacking. In this study, therefore, the production, characteristics and bioactivity of EPSs produced by A. biennis in submerged fermentation were investigated. An EPS-1 was isolated and purified from the culture broth of A. biennis using a Sepharose CL-6B column chromatography. The molecular weight, monosaccharide composition, structural characteristics, chain conformation and thermal property of EPS-1 were determined by gel-filtration chromatography, gas chromatography-mass spectroscopy, Fourier-transform infrared spectroscopy, Congo red test and thermogravimetric analysis, respectively. The in vitro antioxidant and immunoregulation activities of the EPS-1 were evaluated by adopting DPPH and hydroxyl radical-scavenging assays, and analysing NO production in macrophage RAW 264.7 cells, respectively. Results showed that the culture medium containing 30 g/L lactose and 3.0 g/L tryptone had the most suitable carbon and nitrogen sources, respectively, for EPS production in A. biennis. The maximum EPS production (18.29 g/L) was obtained after 6 days of cultivation in a 5 L stirred-tank reactor under the most suitable culture medium. After purification, EPS-1 with 85.4% yield and 96.1% carbohydrate content was obtained from the culture broth of A. biennis. EPS-1 was characterised as a neutral heteropolysaccharide with a molecular weight of 22.07 kDa and is composed of glucose, mannose and galactose at a molar ratio of 3.3:2.0:1.0. EPS-1 with a relatively high thermal stability existed as a random coil conformation in the aqueous medium and possessed prominent radical-scavenging ability and macrophage stimulation activity in vitro. Therefore, EPS-1 could be explored as a functional ingredient with potential applications in food, medical and cosmetic industries.